WEAR RESISTANT CRITERION FOR FUSED SURFACING HARD ALLOYS - V.V. RUBANOV (Advanced Engineering Research)
Wear resistant criterion suggested for choice of the fused surfacing hard alloys for hard usage. The criterion investigation is advisable for composition of hard alloys selection. The increase of wear resistance achieved by means of simultaneous enlargement of hard inclusions content and bending ultimate strength with constant of friction and defect size lessening.